Prototype of scenario dashboard based on MAGNET modelling for Bangladesh - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
A scenario modelling dashboard has been created (see the example for Bangladesh in the URL) for policy makers to explore scenario results created through the MAGNET model.